Anion sensing by metal-based receptors - Beer, P; Bayly, SR (2005)
Metal-based receptors are an important and expanding class of molecules in anion sensing. This review describes the subject with specific focus on the metal-containing subunit's function in determining their anion sensing properties. In general the metal ion is used as a photo- and/or electrochemical reporter group, an anion recognition site and/or as a simple structural component. Metal-based receptors, particularly where the metal ion performs a combination of these roles, exhibit a range of functionality not available to purely organic structures. The most recent advances in the field are also detailed including the use of metallo-receptors in dendrimer, functionalised nanoparticle and surface-bound anion sensors. © Springer-Verlag Berlin Heidelberg 2005.